Foreign labour in Malaysian manufacturing: trends, patterns and implications for domestic wages - Athukorala, P.C.; Devadason, E.S. (2011)
The growing presence of foreign workers has sparked a continuing debate in labour importing Countries in East Asia on the socio-economic consequences of labour inflows and the policy options for dealing with the 'foreign worker problem'. At the heart of this debate is the concern that heavy dependence on foreign workers could suppress domestic real wages with adverse implications for economic restructuring and productivity growth. The purpose of this paper is to inform this debate through a case study of Malaysia, a country where increased presence of temporary foreign workers have played a key role in manufacturing growth over the past two decades. The first four sections of the paper provide an overview of Malaysian labour market policy, structural change and labour absorption, and emerging patterns of foreign worker presence in the manufacturing sector. This is followed by an econometric analysis of the determinants of inter-Industry patterns of foreign worker dependence and wage differentials using a new panel dataset. The analysis focusses on the relative importance of foreign worker dependence in determining wage trends compared to other influences relating to the structure and conduct of domestic manufacturing. It is of course not possible to generalize from a single country case, but our results do call for a reconsideration of general perception that foreign workers suppress wages.